2019
DOI: 10.1002/rmv.2094
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of inhibitory checkpoint molecules in acute and chronic HBV and HCV infections: Implications for therapeutic monitoring and personalized therapy

Abstract: Summary The function of T cells is tightly controlled by positive and negative regulations to ensure both successful pathogen elimination and limitation of immune‐mediated pathology. One of the mechanisms to negatively regulate the magnitude and duration of effector T cells is the expression of inhibitory checkpoint molecules (ICs) on the surface membrane of T cells. During acute viral infections, expression of these molecules is upregulated to limit the effector functions following T‐cell activation. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 138 publications
(438 reference statements)
1
8
0
Order By: Relevance
“…Our study showed upregulation of inhibitory receptor expression on the surface of circulating CD8 + T cells in patients with chronic HBV infection, which was in complete agreement with several reports [ 14 17 ]. However, we observed significantly higher expression of PD1 and TIM3 than of CTLA4 or LAG3 on CD8 + T cells, suggesting that PD1 and TIM3 might have a greater contribution to the T cell dysfunction observed during HBV infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed upregulation of inhibitory receptor expression on the surface of circulating CD8 + T cells in patients with chronic HBV infection, which was in complete agreement with several reports [ 14 17 ]. However, we observed significantly higher expression of PD1 and TIM3 than of CTLA4 or LAG3 on CD8 + T cells, suggesting that PD1 and TIM3 might have a greater contribution to the T cell dysfunction observed during HBV infection.…”
Section: Discussionsupporting
confidence: 93%
“…Prolonged and/or high coexpression of multiple IRs, such as programmed cell death protein 1 (PD1) and T cell immunoglobulin and mucin domain 3 (TIM3), is a key feature of CD8 + and CD4 + T cell exhaustion in humans [ 7 , 13 ]. Several reports have indicated that IR expression is upregulated on HBV-specific CD8 + T cells [ 14 17 ]. Previous studies indicated that CXCR5 + Tfc cells exhibited a reduced state of exhaustion, with lower surface expression of IRs than their counterpart CXCR5 − non-Tfc cells during chronic infection [ 12 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ and TNF-α, produced by T cells, reduce levels of HBV cccDNA in hepatocytes by inducing deamination and subsequent cccDNA decay [ 35 ]. However clinical evidence shows that the CD8+ T cells in CHB patients lose their antiviral function and ability to proliferate, which is characterized by T cell exhaustion, suppressed cytokine production and excessive inhibitory signals [ 36 38 ]. The co-inhibitory receptor PD-1, expressed on T-cells, delivers negative signals when engaged by its ligand PD-L1, expressed on dendritic cells, macrophages, endothelial cells and hepatocytes; to attenuate T cell activation, effector functions and survival [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ and TNF-α, produced by T cells, reduce levels of HBV cccDNA in hepatocytes by inducing deamination and subsequent cccDNA decay [32]. However clinical evidence shows that the CD8+ T cells in CHB patients lose their antiviral function and ability to proliferate, which is characterized by T cell exhaustion, suppressed cytokine production and excessive inhibitory signals [33-35]. The co-inhibitory receptor PD-1, expressed on T-cells, delivers negative signals when engaged by its ligand PD-L1, expressed on dendritic cells, macrophages, endothelial cells and hepatocytes; to attenuate T cell activation, effector functions and survival [36].…”
Section: Discussionmentioning
confidence: 99%